A Population-Based Study of Effects of Genetic Loci on Orofacial Clefts. (October 2017) - Moreno Uribe, L.M.; Fomina, T.; Munger, R.G.; Romitti, P.A.; Jenkins, M.M.; Gjessing, H.K.; Gjerdevik, M.; Christensen, K.; Wilcox, A.J.; Murray, J.C.; Lie, R.T.; Wehby, G.L.
Prior genome-wide association studies for oral clefts have focused on clinic-based samples with unclear generalizability. Prior samples were also small for investigating effects by cleft type and exclusively studied isolated clefts (those occurring without other birth defects). We estimated the effects of 17 top loci on cleft types in both isolated and nonisolated cases in the largest consortium to date of European-descent population-based studies. Our analytic approach focused on a mother-child dyad case-control design, but it also allowed analyzing mother-only or child-only genotypes to maximize power. Our total sample included 1, 875 cases with isolated clefts, 459 cases with nonisolated clefts, and 3, 749 controls. After correcting for multiple testing, we observed significant associations between fetal single-nucleotide polymorphisms (SNPs) at IRF6, PAX7, 8q21.3, 8q24, KIAA1598-VAX1, and MAFB and isolated cleft lip only (CLO) and cleft lip and palate (CLP). Significant associations were observed between isolated CLO and fetal SNPs near TPM1 and NOG1 and between CLP and fetal SNPs at ABCA4-ARHGAP29, THADA, FOXE1, and SPRY2 . Overall, effects were similar for isolated CLO and CLP, except for ABCA4-ARHGAP29 . A protective effect was observed for the fetal NOG1 SNP on cleft palate only, opposite in direction to the effect on CLO. For most fetal SNPs, a dose-response allelic effect was observed. No evidence of parent-of-origin or maternal genome effects was observed. Overall, effect direction and magnitude were similar between isolated and nonisolated clefts, suggesting that several loci are modifiers of cleft risk in both isolated and nonisolated forms. Our results provide reliable estimates of the effects of top loci on risks of oral clefts in a population of European descent.